Legal Review of Abusive Dating Relationships - Ahsan, Allya Maulida Putri; Hapsari, Ifahda Pratama (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Researching and discussing abusive and violent romantic relationships within a legal framework is becoming an increasingly pressing social issue. The purpose of this article is to provide a comprehensive legal examination of the numerous forms of abuse in dating relationships, including physical, psychological, sexual, economic, and digital forms of abuse. The author employs normative juridical research for his study. Based on what has been said, it is clear that abusive dating relationships are a pervasive and troubling social issue that calls for legislative action. The safety of victims and the efficiency of law enforcement are of the utmost importance.